(3JMQjQ GdebGdI aj TQM GdQSGdIs - (3CMeO Hf eMeO Hf YHO Gddg,GdbdTGfj , CHh GdYHGS,J (B863 (3g` s
(3ChdgG (B:s
(3HGH aj GdfcGM hGdWdGb hGdQLYI hGdWgGQI s
(3BNQgG (B:s
(3GdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjekG s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdeGdcjs